Analisis Potensi Bahaya pada Perbaikan Threading di PT. XYZ Menggunakan Metode JSA - Rizki Juniarto, Muhammad; Andivas, Marulan; Defran Vandhana, Muhammad (SURYA TEKNIKA, 2024)
The high use of for gas and petroleum fuels in Balikpapan, East Kalimantan, encouraging accelerated development of oil and gas infrastructure including transmission pipeline systems, drilling wells and offshore oil and gas platforms. Gas pipes experience problems such as leaks, blockages and corrosion, so they require maintenance and accurate installation. The Job Safety Analysis (JSA) method is used to identify and reduce potential hazards and risks during work implementation. Implementing JSA not only ensures compliance with occupational safety and health regulations, but also creates a safer work environment and reduces the potential for accidents. This research aims to determine the level of risk in each job by obtaining consequence and probability values. Risk evaluation in threading work can be summarized into three categories, low risk covers 46.66% of the calculation results, while medium risk reaches 53.33%, and high risk reaches 13.33%.